2022
DOI: 10.3389/fgene.2021.811833
|View full text |Cite
|
Sign up to set email alerts
|

A Family Segregating Lethal Primary Coenzyme Q10 Deficiency Due to Two Novel COQ6 Variants

Abstract: Primary coenzyme Q10 deficiency-6 (COQ10D6), as a rare autosomal recessive disease caused by COQ6 mutations, is characterized by progressive infantile-onset nephrotic syndrome resulting in end-stage renal failure and sensorineural hearing loss. Here, we report two Chinese siblings with COQ10D6 who primarily presented with severe metabolic acidosis, proteinuria, hypoalbuminemia, growth retardation, and muscle hypotonia and died in early infancy. Using whole-exome sequencing and Sanger sequencing, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The brother of this patient, also suffering COQ6 deficiency, received a computed tomography (CT) of the brain at the age of 5 months, which showed a similar pathology with signs of frontotemporal brain atrophy [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The brother of this patient, also suffering COQ6 deficiency, received a computed tomography (CT) of the brain at the age of 5 months, which showed a similar pathology with signs of frontotemporal brain atrophy [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using ES in NPHS2 negative cases, we identified multiple biallelic disease-causing NPHS1 variants, two heterozygous disease-causing WT1 variants as well as biallelic disease-causing variants in COQ6, ARHGDIA, NUP205 , and SGPL . Disease-causing variants in COQ6 represent a very rare cause of SRNS with until completion of this study less than 20 disease-causing alleles reported to date in the literature ( 30 , 31 ) ( Figure 2 ). Very recently, Drovandi et al reported additional COQ6 cases as part of a large cohort of 116 individuals with primary coenzyme Q10 deficiency in which CoQ10 replacement had beneficial effects regarding disease progression ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 97%
“…In this case, supplementation with the CoQ10 analogue idebenone, which has been used for the treatment of other types of optic neuropathy, improved visual impairment without affecting deafness. Wang et al [ 69 ] identified two Chinese siblings with COQ10D6 who presented with severe metabolic acidosis, proteinuria, hypoalbuminemia, growth retardation, and muscle hypotonia and died in early infancy (mutations: [c.249C>G] [p.Tyr83Ter] in Exon 2 and [c.1381C>T] [p.Gln461Ter] in Exon 12 of COQ6 ). A 19-month-old patient with cardiomyopathy was found to have the COQ6 variant [c763G>A] [p.Gly255Arg]; the patient died from cardiorespiratory failure before CoQ10 supplementation could be started [ 70 ].…”
Section: Clinical Studies Relating To Coq Gene Mutationsmentioning
confidence: 99%
“…In this case, supplementation with the CoQ10 analogue idebenone, which has been used for the treatment of other types of optic neuropathy, improved visual impairment without affecting deafness. Wang et al [69] identified two Chinese siblings with COQ10D6 who presented with severe metabolic acidosis, proteinuria, hypoalbuminemia, growth retardation, and muscle hypotonia and died in early infancy (mutations: The total number of patients identified with a COQ6-related primary CoQ10 deficiency is currently 45, with 14 of these responding to CoQ10 supplementation (where attempted).…”
Section: Coq6mentioning
confidence: 99%